Horaires de travail, sommeil et vigilance chez les marins : quelles incidences sur les risques d’accidents en mer ? - Ghislaine Tirilly (Perspectives Interdisciplinaires sur le Travail et la Santé)
After the recent maritime disasters, the maritime field is focused on safety. Nevertheless, preventive measures adopted in order to improve safety at sea involve ship supervision, safe shipping and protection of the marine environment (risk of pollution). However, these means are slow in being implemented and do not take into account men at work. A first approach could be to observe the organization of working time on board ships. In most cases, work schedules at sea are based on keeping watch, which leads to fragmented work and sleep episodes over a 24 hour period. Consequently, work often occurs at hours that are not conducive to maintaining a suitable level of alertness. The decrease in alertness has been related to fatigue and a much greater risk of accidents.The present study examines the adjustment of sleep/wake rhythms and alertness in two shift schedule conditions at sea. Results will be discussed in relation to the accident risks associated with this work system.